Microbial kinetics, fermentative and chemical characteristics in solid state fermentation of apple bagasse - CASTILLO-CASTILLO, Y; RUIZ-BARRERA, O; SALINAS-CHAVIRA, J; ANGULO-MONTOYA, C; BURROLA-BARRAZA, E; MURILLO-ORTIZ, M; MONTAÑO-G, M; ELÍAS-IGLESIAS, A (The Indian Journal of Animal Sciences, 2012)
The objective of this study was to evaluate the microbial kinetics, fermentative and chemical characteristics during solid state fermentation (SSF) of apple bagasse (AB), which was determined over the course of 4 incubation times: 0, 24, 48, 72 h, in a completely randomized design with 4 repetitions. pH values, lactic acid concentration, numbers of total aerobic bacteria, yeast and lactobacilli, dry matter digestibility and neutral detergent fiber digestibility were determined. True and crude protein, neutral and acid detergent fiber were also measured. Results revealed that pH decreased over the 4 sampling times. The lactic acid concentration increased over time. There was a reduction in numbers of total aerobic bacteria. Numbers of lactobacilli also reduced. Yeast populations (CFU/ml) were stable at 24 h, but decreased thereafter. In vitro dry matter digestibility (IVDMD) increased during incubation. In vitro neutral detergent fiber digestibility (IVNDFD) similarly increased, with a maximum value observed at 72 h. True protein (TP) increased during fermentation, achieving a high value at 24 h; however, crude protein (CP) showed no change during incubation. Neutral detergent fiber (NDF) content did not change during fermentation however acid detergent fiber (ADF) reduced. It is concluded that the increased content of lactic acid and the accompanying decrease in pH during SSF of AB negatively affected the yeast and total bacteria populations whereas true protein content increased likely because of formation of unicellular protein during the process.